2007
DOI: 10.1097/inf.0b013e31812f4f5b
|View full text |Cite
|
Sign up to set email alerts
|

Invasive Infections Caused by Haemophilus influenzae Serotypes in Twelve Canadian IMPACT Centers, 1996–2001

Abstract: In 1996-2001, two-thirds of H. influenzae invasive disease in the 12 IMPACT centers was caused by non-b serotypes, which were associated with significant morbidity and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
60
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(66 citation statements)
references
References 29 publications
5
60
1
Order By: Relevance
“…19.6 % of the population (Statistics Canada, 2006). Previous studies found a high incidence of invasive Hia disease among North American aboriginal people, including Canadian First Nations (Hammitt et al, 2005;Millar et al, 2005;McConnell et al, 2007;Bruce et al, 2008). According to Bruce et al (2008), the incidence rate of invasive Hia disease in the North American Arctic was 2.9/ 100 000 for indigenous and 0.2/100 000 for non-indigenous people.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19.6 % of the population (Statistics Canada, 2006). Previous studies found a high incidence of invasive Hia disease among North American aboriginal people, including Canadian First Nations (Hammitt et al, 2005;Millar et al, 2005;McConnell et al, 2007;Bruce et al, 2008). According to Bruce et al (2008), the incidence rate of invasive Hia disease in the North American Arctic was 2.9/ 100 000 for indigenous and 0.2/100 000 for non-indigenous people.…”
Section: Discussionmentioning
confidence: 99%
“…with an annual incidence rate of 20.2/100 000 for children under the age of 5 years (Millar et al, 2005). In the Keewatin Region of Nunavut (northern Canada), the estimated incidence of invasive Hia disease was 418.7/100 000 for Inuit children under 5 years old (McConnell et al, 2007). In four Canadian western provinces (British Columbia, Alberta, Saskatchewan and Manitoba), the rate of invasive Hia disease among aboriginal children under 5 years of age was 3.7/100 000 (McConnell et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several recent surveys have utilized various study designs to monitor invasive H. influenzae disease in several countries throughout the world in the Hib conjugate vaccine era (1,3,10,19,20,22,23,27,35,46). The following statements summarize the main conclusions from these studies.…”
Section: Impact Of Hib Conjugate Vaccines On Invasive Non-hib Diseasementioning
confidence: 98%